Formulation and Hedonic Test of Lemon (Citrus limon L.), Ginger (Zingiber officinale), and Porang (Amorphophallus muelleri Blume) Flour as Health Powder Beverage - Nurshiyami, Yusfa; Nuraini, Nuraini; Yuniarto, Ari (Fakultas Farmasi, Universitas Surabaya, 2024)
Health powder drinks are drinks made from powder or granules in a mixture of sugar, fruit, and spices, usually served quickly by brewing, and contain many nutritional and non-nutritional elements. Identify the physical evaluation of powder, quality requirement test (Indonesian National Standard (SNI)), and hedonic test of lemon juice (Citrus limon L.), ginger (Zingiber officinale), and porang flour (Amorphophallus muelleri Blume) health powder beverage. This study was experimental, by making lemon and ginger juice powder using a freeze-drying instrument. Lemon, ginger, and porang flour powders were formulated in 3 formulas. Then, the physical evaluation of the powder involving a quality requirement test (SNI) and hedonic test was conducted. The results of physical evaluation tests which include (organoleptic, flow time, angle of repose, specific gravity, water content, and dissolving time) and quality requirements tests which include (water content and ash content) show that powdered drinks meet the physical requirements of powders and quality requirements (SNI). Hedonic taste, color, aroma, and texture tests differ from the three formulas. Health powder drinks have a good physical evaluation of powders and quality requirements (SNI), and the most favored formula by panelists is formula 3. Submitted: 29-07-2024, Revised: 09-12-2024, Accepted: 11-12-2024, Published regularly: December 2024